The History of Urinary Stones: In Parallel with Civilization - Ahmet Tefekli; Fatin Cezayirli (The Scientific World Journal)
The roots of modern science and history of urinary stone disease go back to the Ancient Egyptians and Mesopotamia. Hippocrates defined the symptoms of bladder stones. The first recorded details of “perineal lithotomy” were those of Cornelius Celsus. Ancient Arabic medicine was based mainly on classical Greco-Roman works. Interestingly, the Fourth Lateran Council in 1215 forbade physicians from performing surgical procedures, as contact with blood or body fluids was viewed as contaminating to men. With Renaissance new procedures could be tried on criminals. The first recorded suprapubic lithotomy was carried out by Pierre Franco in 1561. In 1874, Bigelow developed a lithotrite, which was introduced into the bladder under anaesthesia (called as “litholopaxy”). Young was the first to report ureteroscopy (1929). With advances in intracorporeal lithotripsy techniques, ureteroscopy became the treatment of choice for ureteric stones. In 1976, Fernstrom and Johannson established percutaneous access to remove a renal stone. However, with the introduction of the first extracorporeal shock wave machine in 1980, a dramatic change in stone management was observed. Civilization in parallel with scientific developments has brought us to a point where we try not to “cut” our patients for stone disease, as Hippocrates admonishes, but rather manage them with minimal invasive alternatives.